Luther's Tears: Hagar and the Limits of Empathy - Elser, Ashleigh (Studies in Christian ethics, 2022)
In his Enarrationes in Genesin, Martin Luther finds stories of suffering he can ‘hardly read with dry eyes’. Recent scholars attribute profound ethical value to Luther's tears, especially those shed over the suffering of female characters. This article reconsiders the ethical salience of Luther's tears as a demonstration of interpretive empathy by examining his reading of Hagar and its modern reception history. By comparing Luther's reading of the enslaved Hagar to his reading of her master Abraham, it is argued that gender, power and inequality shape the very conditions in which terms like ‘empathy’, ‘charity’ and ‘suspicion’ appear and this, in turn, invites a reconsideration of the ethical responsibilities we incur as we read texts of terror in light of their role in enduring histories of violence.